Penataan Lapangan Taruna Remaja di Kawasan Heritage Kota Gorontalo dengan Pendekatan Arsitektur Indis - Nirmawaty Laha; Zuhriati A. Djailani; Dara Fitriani (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2026)
The Heritage Area of Gorontalo City features a prominent public space known as Lapangan Taruna Remaja. This public space serves as the city's central square, facilitating various social activities such as recreation, sports, relaxation, and culinary experiences. Lapangan Taruna Remaja holds significant potential due to its historical value and location within Gorontalo City's Heritage Area, offering opportunities to enhance its status as a tourist destination while contributing to the area's economic and social development. Despite its potential, the square faces several challenges, including the deterioration of its physical quality due to vandalism and the repurposing of its facilities by street vendors. Additionally, the square experiences water pooling during heavy rainfall, leading to flooding. These issues arise from inadequate utility infrastructure within the square. This study aims to redesign Lapangan Taruna Remaja as a public space in Gorontalo City's Heritage Area by incorporating the principles of Indis architecture as the primary design framework. The data collection employed a qualitative descriptive method, encompassing primary and secondary data. Primary data were gathered through observation, interview, and documentation, while secondary data were obtained from institutional and library resources, as well as media reviews from journals, scientific articles, and reliable news sources. The analysis and spatial programming include site analysis, spatial needs, space dimensions, and spatial relationships. The final design concept incorporates Indis architecture to shape the outdoor spaces and building structures of Lapangan Taruna Remaja. Architectural elements such as roof styles, windows, doors, and ventilation reflect the adaptation of Indis architectural styles present in the surrounding area.